Pengaturan dan Urgensi Whistle Blower dan Justice Collaborator dalam Sistem Peradilan Pidana - Rusli Muhammad (Jurnal Hukum IUS QUIA IUSTUM, 2015)
The first and foremost problem in this study is the setting of Whistle Blower and Justice Collaborator in Indonesia. The second is the urgency and the existence of Whistle Blowers and Justice Collaborator in the Criminal Justice System. To analyze those problems the researcher used a normative juridical research. On the basis of the study it is revealed that, first, there are some rules governing the Whistle Blower and Justice Collaborator in the Criminal Justice System, but there is no room for its setting in the Criminal Code (KUHAP). Second, the urgency and the existence of Whistle Blowers and Justice Collaborator can be found through the workings of both the Criminal Justice System in the Investigation, Prosecution, Trial and in the implementation of decisions